Investigation of sedimentation patterns around hydraulic structures in the Jaro River System using a 2D sediment transport model - Diaz, Patrick Joseph B.; Tabios, Guillermo Q. III (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Iloilo City had been identified as one of the critically flooded urban centers in the Philippines with floods occurring almost yearly, due in part to the insufficient capacity of the Jaro River. The Jaro floodway was constructed, as part of the Iloilo Flood Control Project, with the aim of mitigating flood damage in the city. Since the beginning of its operation in 2011, it has been effective in diverting flood discharges to the Iloilo Strait, successfully complying with its design. However, the occurrence of sedimentation-related problems including riverbank erosion and bridge scouring near the flood way following its opening shows that sedimentation should have also been a major consideration in the development of the river. This paper reports the investigation that was done of the sedimentation patterns around hydraulic structures in the Jaro River System. The investigation, which primarily aims to assess the integrity and effectiveness of the structures, was done using a 2D sediment transport model called SEDFVM-2D or Sediment-Laden River Basin 2D Model, that operates based on the finite volume method. A 50-year design flood was simulated over 72 hours, and then the combined effects of degradation, contraction scour and local scour at the structures were evaluated. It was concluded that in the passage of this extreme flood, the bridges may be compromised particularly due to significant amounts of local scouring at the abutments. Also, while significant deposition may occur from immediately downstream of the hydraulic drop structures to the mouth of the floodway the floodway is found to still have sufficient capacity to discharge flood waters into the Iloilo Strait, safely keeping a 1 meter freeboard up to the dike crest even at the maximum deposition levels and flow depths.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Sediment transport -- Philippines -- Iloilo; Sedimentation and deposition